Dorosłe dzieci alkoholików - ofiary czy mistrzowie przetrwania? - Przybysz-Zaremba, Małgorzata; Szeszko-Zaborowska, Monika (Kultura-Społeczeństwo-Edukacja, 2024)
Children are the hardest hit due to their parents’ alcoholism. They experience chronic stress or even trauma in both childhood and adulthood. The article is of a research nature. The aim was to learn about the roles played by children in an alcoholic family and their consequences in adulthood. The research was carried out by the diagnostic survey with the use of a proprietary online questionnaire on self-help ACoAs groups within one of social media platforms (the study group: 125 adult children of alcoholics). Results: It has been shown that ACoAs played adaptive roles in childhood – nearly half of them (43.5%) indicated the role of the “family hero”. Almost all respondents (92.8%) confirmed that growing up in an alcoholic family has consequences in their adult life – 41.6% indicated both negative and positive consequences, for 51.2% consequences are rather negative. The most frequently indicated positive consequences: responsibility, empathy, independence, coping with stressful situations. The overwhelming majority of respondents indicated among negative consequences: low self-esteem, fear of rejection, not coping with emotions. Despite ACoAs assess their lives as rather successful or very successful. Conclusions: ACoAs experience in adulthood the consequences of growing up in an alcoholic family – but not only negative ones. However, the issue is ambiguous and requires further studies.